Początki działalności instytucji użyteczności publicznej w Gorzowie Wielkopolskim w latach 1948-1956 = Beginnings of the activity of public utility institutions in Gorzów Wielkopolski in the years 1948-1956 - Domke, Radosław (Zielona Góra: Lubuskie Towarzystwo Naukowe)
This article is concentrated on the activity of town services in Gorzow Wielkopolski. Additional subjects are: public transport, postal and communication services, and road traffic. Drifts about health service are not included in this article, because they are greatly researched by Andrzej Marciniak, who discusses them in the ?Nadwarciański Historical and Archival Annual?.
Keywords: Gorzów Wielkopolski; instytucje publiczne; historia; 1945-1970